Fundamentals of Entrepreneurship (ENT300) : Borneo Fitness / Ain Shafika Binti Ahmad... [et al.] - Ahmad, Ain Shafika; Awg Razak, Awg Abdul Aziz; Hamzah, Azam; Luis, Fareedah; Mohamed Ansari, Mohamed Saffwan (2015)
Name of the business : Borneo Fitness is our company's name which is decided after a discussion among our shareholders. The name is chosen as it is suitable with our goals. Type/Nature of the business: The nature of our business is to provide services, listen, and help support people in any way we can. Also to achieving results, and helping people get the body they really deserve. Industry Profile: Small enterprises from local entrepreneurs, Local Sarawakian/local gym and fitness, Indirect competitors. Location of the Business: The location of our business is located at Corner of Lorong Foochow No.l & Jalan Tun Razak, 93675 Kuching. We choosed this place because this place was strategic and people easy to find it. Date of Business Commencement: Our business will be expected to commence on 25th December 2016 due to the selection of the strategic operation place and building for our business. Apart from that, we have to set up and come out with a strategic marketing plan in order to provide activies and services to our customers.